1996
DOI: 10.1073/pnas.93.16.8413
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma invasion: the parasitophorous vacuole is formed from host cell plasma membrane and pinches off via a fission pore.

Abstract: Most intracellular pathogens avoid lysing their host cells during invasion by wrapping themselves in a vacuolar membrane. This parasitophorous vacuole membrane (PVM) is often retained, serving as a critical transport interface between the parasite and the host cell cytoplasm. To test whether the PVM formed by the parasite Toxoplasma gondii is derived from host cell membrane or from lipids secreted by the parasite, we used time-resolved capacitance measurements and video microscopy to assay host cell surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(190 citation statements)
references
References 32 publications
7
179
0
4
Order By: Relevance
“…Evacuoles are also seen during normal invasion and may be formed from the initial burst of secretion from the rhoptries that occurs in the initial stages of invasion [14] (Figure 1B). During this initial burst, the host plasma membrane is transiently disrupted potentially allowing access to the cytosol before the envelope reseals to envelope the parasite [15,16]. Based largely on these studies, it was proposed that: "secretion of rhoptries at the time of invasion served as a means to deliver effector proteins into the host cell" [14].…”
Section: Rhoptries: An Apical Secretory Organelle Involved In Invasionmentioning
confidence: 99%
“…Evacuoles are also seen during normal invasion and may be formed from the initial burst of secretion from the rhoptries that occurs in the initial stages of invasion [14] (Figure 1B). During this initial burst, the host plasma membrane is transiently disrupted potentially allowing access to the cytosol before the envelope reseals to envelope the parasite [15,16]. Based largely on these studies, it was proposed that: "secretion of rhoptries at the time of invasion served as a means to deliver effector proteins into the host cell" [14].…”
Section: Rhoptries: An Apical Secretory Organelle Involved In Invasionmentioning
confidence: 99%
“…Joiner (36) and Sinai and Joiner (37) suggested that insertion of parasite lipids into the PVM might affect PVM interaction with other cell membranes, preventing fusion with endocytic compartments. Suss-Toby (38) reported that a small amount of parasite-derived material (0-18.5% of the total surface area of the PVM) may be inserted into the host cell plasma membrane. Our observations cannot definitively rule out bulk insertion of lipids We used DTAF, which reacts both with primary and secondary amine groups (20), to label membrane proteins of the macrophages before interaction with parasites in order to follow the fate of the labeled proteins during the parasite-host cell interaction process.…”
Section: Formation Of the Parasitophorous Vacuolementioning
confidence: 99%
“…After the apical end of a parasite comes in contact with the host cell membrane, apical secretory organelles (micronemes and rhoptries) sequentially discharge their contents (Dubremetz et al, 1993;Carruthers and Sibley, 1997) and a zone of tight interaction forms between the two cells (Nichols and O'Connor, 1981;Dubremetz et al, 1985;Grimwood and Smith, 1995). An invagination in the host cell plasma membrane develops at the point of entry and progressively deepens, ultimately surrounding the fully internalized parasite (Suss-Toby et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…After the apical end of a parasite comes in contact with the host cell membrane, apical secretory organelles (micronemes and rhoptries) sequentially discharge their contents (Dubremetz et al, 1993;Carruthers and Sibley, 1997) and a zone of tight interaction forms between the two cells (Nichols and O'Connor, 1981;Dubremetz et al, 1985;Grimwood and Smith, 1995). An invagination in the host cell plasma membrane develops at the point of entry and progressively deepens, ultimately surrounding the fully internalized parasite (Suss-Toby et al, 1996).Apical membrane antigen-1 (AMA1) is a microneme protein that is highly conserved among apicomplexan parasites (Waters et al, 1990;Donahue et al, 2000;Hehl et al, 2000;Gaffar et al, 2004). Since its initial discovery Ͼ15 years ago, AMA1 has received considerable attention as a malaria vaccine candidate (Deans et al, 1988;Collins et al, 1994;Anders et al, 1998;Kennedy et al, 2002;Stowers et al, 2002).…”
mentioning
confidence: 99%